Analyzing Abi Azkakia's Online Game Preaching Using Giddens' Structuration Theory Perspective: Menganalisis Dakwah Game Online Abi Azkakia Menggunakan Perspektif Teori Strukturasi Giddens - Perdana, Wahyu Ilham; Dharma, Ferry Adhi (House of Wisdom: Journal on Library and Information Sciences, 2025)
This study discusses Ustadz Abi Azkakia's da'wah strategy through online games with Anthony Giddens' structuration perspective. Digital da'wah, especially in the gaming community, is a new phenomenon that is interesting to study. Using the autoethnography method, this study directly observes the interactions and strategies used by Ustadz Abi in conveying Islamic messages in virtual space. The results of the study show that Ustadz Abi Azkakia utilizes religious symbols, such as peci, as well as a communication approach that is in accordance with gamer culture to build an identity as a da'wah. He consistently inserts the values of tauhid, qada and qadar, and Islamic ethics in the game. Giddens' structuration perspective explains that da'wah in online games occurs through interactions between agents (Ustadz Abi) and structures (game communities and digital platforms). Da'wah through this game is quite acceptable to most respondents. However, there are challenges in maintaining a balance between entertainment and religious messages. Some respondents see him as a relaxed and easy-to-receive figure, while others feel that the da'wah message sometimes interferes with the gaming experience. Nevertheless, Ustadz Abi has built legitimacy as a respected religious figure in the Mobile Legends community. Highlights: Innovative da'wah: Uses gaming culture and symbols to deliver Islamic teachings. Structuration view: Da'wah shaped by agent-platform-community interaction. Mixed reception: Some gamers welcome it, others find it intrusive. Keywords: Preaching Strategy, Online Games, Autoethnography, Giddens' Structuration, Digitalization of Preaching